Wireless Sensor Network Applications in Smart Grid: Recent Trends and Challenges. (2nd September 2012) - Liu, Yide
Abstract : Smart grid revolutionizes the current electric power infrastructure by integrating with communication and information technologies. With wireless sensor network, smart grid enables both utilities and customers to transfer, monitor, predict, and manage energy usage effectively and costly. However, the increased application of wireless sensor network also introduce new security challenges, especially related to privacy, connectivity, and security management, causing unpredicted expenditure and disaster to both utilities and consumers. In order to build a reliable wireless sensor network for smart grid, an application review and taxonomy of relevant cyber security and privacy issues is presented in this paper. A unified framework for identification of applications and challenge issues of wireless sensor network in smart grid is developed. Future research directions are discussed at the end of this paper.